A modified chitosan-based conductive hydrogel flexible strain sensor and a preparation method and application thereof

CN117647178BActive Publication Date: 2026-10-23SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311783559.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-22
Publication Date
2026-10-23
Estimated Expiration
2043-12-22

AI Technical Summary

Technical Problem

[0008]尽管上述几种方法都能制备性能良好的柔性应变传感器,但针对未来人体生理监测,如何构建高灵敏度、性能稳定,优异生物相容性、可抗菌自愈合循环使用且制备工艺简单、低成本的柔性材料仍然是关键与挑战

Benefits of technology

[0034]本发明将没食子酸改性的壳聚糖、苯硼酸改性的壳聚糖复合载银聚多巴胺纳米粒直接作为电阻式柔性应变传感器。该传感器具有良好的形变能力、灵敏度高、线性度好、应变检测范围广并且响应迅速,还具有良好的生物相容性、皮肤粘附性和抗菌性能,适用于柔性可穿戴设备、医疗健康监测和人机交互等领域。此外本发明提出的柔性应变传感器制作步骤简单、可靠、生产制造成本低,适用于大批量生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117647178B_ABST
    Figure CN117647178B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of modified chitosan-based conductive hydrogel flexible strain sensor and its preparation method and application, the preparation raw material of the conductive hydrogel flexible strain sensor includes modified chitosan and silver-loaded polydopamine nanoparticle.The flexible strain sensor of the present application has high linearity, high sensitivity, fast response speed, antibacterial property and biocompatibility in large strain range, in addition, its preparation method is simple and reliable, and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of research technology of biomaterials and flexible wearable health electronic devices, and relates to a conductive hydrogel flexible strain sensor based on modified chitosan, its preparation method and application. Background Technology

[0002] Compared to traditional electronic devices, flexible electronic devices possess high flexibility, conformability, and adaptability, enabling them to adapt to different shapes, surfaces, and environments to meet users' deformation requirements. Flexible strain sensors, as a core component of flexible electronic devices, convert strain changes into electrical signals for output. When attached to human skin or irregular surfaces, they can acquire real-time physiological information and motion status, thus finding wide applications in health monitoring, motion monitoring, robotics, and human-computer interaction. Traditional strain sensors often use rigid materials such as metals and single-crystal silicon. While these offer high sensitivity, they cannot adapt to human skin or irregularly shaped surfaces. Flexible strain sensors, fabricated from flexible materials, possess exceptional flexibility, thinness, conformability, and tensile strength, allowing them to conform well to human skin and improve user comfort. However, currently, most biocompatible flexible strain sensors suffer from low sensitivity, low linearity, long response times, and narrow strain ranges, severely impacting their ability to comprehensively detect and analyze complex physiological signals and physical movements. In recent years, researchers have developed high-performance flexible strain sensors using various fabrication methods, such as:

[0003] (1) A transparent precursor is formed by mixing a certain proportion of polyvinyl alcohol, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide (SBMA), and 2-hydroxyethyl methacrylate under acidic conditions. After defoaming at room temperature, potassium persulfate and tetramethylethylenediamine are added, and the mixture is crosslinked in a mold at 50°C. Following multiple freeze-thaw cycles at -20°C / room temperature, a hydrogel is formed. When applied to a flexible strain sensor, this hydrogel exhibits sensitivities of 1.434, 2.448, and 3.356 at strains of 0-100%, 100-200%, and 200-300%, respectively, and can be used for underwater motion monitoring.

[0004] (2) A flexible hydrogel reinforced with silica nanofibers, vinyl silane, sodium alginate, and polyacrylamide was prepared. The polyacrylamide chains were coupled to the silica nanofibers via silane to form a stable interface, while hydrogen bonds between the silica nanofibers and polyacrylamide chains provided energy dissipation. This flexible hydrogel exhibits excellent mechanical properties, with a high mechanical strength of 0.3 MPa at 1400% fracture strain and a high Young's modulus of 0.11 MPa (comparable to human skin), while maintaining high transmittance (≥83%). When applied to a flexible strain sensor, it exhibits sensitivities of 0.82 and 2.67 at strains of 0-300% and 300-1100%, respectively, and can withstand 10,000 cycles under a pressure of 6.37 kPa.

[0005] (3) A honeycomb-like ordered porous polyvinyl alcohol / MXene hydrogel was prepared by directional freezing and salting out. The directional micron-sized pore structure and the synergistic effect between polyvinyl alcohol and MXene give the material excellent flexibility. The maximum sensitivity at deformation of 0-12.5% ​​and 30-50% is 1.07 and 1.74, respectively, which can be used for human motion monitoring.

[0006] (4) A conductive hydrogel with self-healing properties, good mechanical properties, and excellent adhesion was prepared based on polydopamine nanoparticles, 1-vinyl-3-butylimidazolium trifluoromethanesulfonylimide salt ionic liquid, and polyacrylamide. As a flexible strain sensor, its strain sensitivities at 0-60%, 60-140%, and 140-200% were 0.442, 0.689, and 0.841, respectively.

[0007] (5) A polyaniline / polyvinyl alcohol hydrogel was constructed. Ammonium persulfate initiated the polymerization of polyaniline, and glutaraldehyde achieved chemical cross-linking of polyvinyl alcohol to form an interpenetrating double network. Further, ice template-assisted low-temperature polymerization was used to form a layered, dendritic, densely interconnected microstructure. Compared with the hydrogel obtained by liquid-phase synthesis, its tensile toughness was increased by 29 times and its electrical conductivity by 83 times. When applied to a flexible strain sensor, this hydrogel exhibited a sensitivity of 1.43 in the strain range of 0-100%.

[0008] Although the above methods can all produce high-performance flexible strain sensors, the key and challenge for future human physiological monitoring is how to construct flexible materials that are highly sensitive, stable, biocompatible, antibacterial, self-healing, reusable, and have simple and low-cost fabrication processes. Summary of the Invention

[0009] To address the shortcomings of existing technologies, the present invention aims to provide a flexible strain sensor based on modified chitosan conductive hydrogel, its preparation method, and its application.

[0010] To achieve this objective, the present invention adopts the following technical solution:

[0011] In a first aspect, the present invention provides a conductive hydrogel flexible strain sensor based on modified chitosan, wherein the raw materials for preparing the conductive hydrogel flexible strain sensor include modified chitosan and silver-loaded polydopamine nanoparticles.

[0012] This invention presents a highly sensitive, wide-range, fast-response, and biocompatible resistive hydrogel flexible strain sensor prepared by combining gallic acid-modified chitosan and phenylboronic acid-modified chitosan with silver-loaded polydopamine nanoparticles. The sensor's fabrication method is simple, requires no stringent environmental or equipment conditions, is low-cost, and highly repeatable. Therefore, this flexible strain sensor has promising applications in various fields such as medical and health monitoring, robotics, and human-computer interaction.

[0013] Preferably, the raw materials for preparing the conductive hydrogel flexible strain sensor include 1-20 parts of modified chitosan and 0.1-2 parts of silver-loaded polydopamine nanoparticles by mass.

[0014] The mass fraction of the modified chitosan can be selected from 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc., and the mass fraction of the silver-loaded polydopamine nanoparticles can be selected from 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, etc. Other specific values ​​within the above range can be selected, and will not be elaborated here.

[0015] Preferably, the modified chitosan includes gallic acid-modified chitosan and phenylboronic acid-modified chitosan.

[0016] Preferably, the mass ratio of gallic acid-modified chitosan to phenylboronic acid-modified chitosan is (0.5-2):(0.5-2), where the specific values ​​in (0.5-2) can be selected from 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, etc. Other specific values ​​within the above range can also be selected, and will not be elaborated here.

[0017] In a second aspect, the present invention provides a method for preparing a conductive hydrogel flexible strain sensor based on modified chitosan according to the first aspect, the method comprising: mixing a modified chitosan solution and a silver-loaded polydopamine nanoparticle solution to obtain the sensor.

[0018] Preferably, the preparation method specifically includes:

[0019] (1) The silver-loaded polydopamine nanoparticle solution was sonicated and vortexed with phenylboronic acid-modified chitosan, and then centrifuged to obtain the first mixture.

[0020] Gallic acid-modified chitosan was vortexed with a glycerol solution and centrifuged to obtain a second mixture.

[0021] (2) Vortex mix the first mixture with the second mixture, centrifuge, and obtain a conductive hydrogel material.

[0022] The purpose of centrifugation is to remove air bubbles from the solution.

[0023] Preferably, the power of the ultrasound is 300-800W and the duration is 1-10min.

[0024] The power of the ultrasound can be selected from 300W, 350W, 400W, 450W, 500W, 550W, 600W, 650W, 700W, 750W, 800W, etc., and the time can be selected from 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min, etc. Other specific values ​​within the above range can be selected, which will not be elaborated here.

[0025] Preferably, the silver-loaded polydopamine nanoparticle solution also includes glycerol.

[0026] Preferably, the mass percentage of glycerol is independently 5-30%, such as 5%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, etc. Other specific values ​​within the above range can be selected, and will not be elaborated here.

[0027] Preferably, the vortex duration is independently 5-60s, such as 5s, 10s, 15s, 20s, 25s, 30s, 35s, 40s, 45s, 50s, 55s, 60s, etc. Other specific values ​​within the above range can be selected, and will not be elaborated here.

[0028] Preferably, the centrifugation speed in step (1) is independently 1000-4000 rpm and the time is independently 10-20 min.

[0029] The rotation speed can be selected from 1000rpm, 1500rpm, 2000rpm, 2500rpm, 3000rpm, 3500rpm, 4000rpm, etc., and the time can be selected from 10min, 12min, 14min, 16min, 18min, 20min, etc. Other specific values ​​within the above range can also be selected, which will not be elaborated here.

[0030] Preferably, the centrifugation speed in step (2) is 1000-4000 rpm and the time is 20-300 s.

[0031] The rotational speed can be selected from 1000rpm, 1500rpm, 2000rpm, 2500rpm, 3000rpm, 3500rpm, 4000rpm, etc., and the time can be selected from 20s, 40s, 60s, 80s, 100s, 120s, 150s, 180s, 200s, 220s, 250s, 280s, 300s, etc. Other specific values ​​within the above range can also be selected, which will not be elaborated here.

[0032] Thirdly, the present invention provides an application of the flexible strain sensor based on modified chitosan conductive hydrogel according to the first aspect in flexible wearable devices, medical and health monitoring, or human-computer interaction.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] This invention utilizes gallic acid-modified chitosan and phenylboronic acid-modified chitosan composites loaded with silver-impregnated polydopamine nanoparticles directly as a resistive flexible strain sensor. This sensor exhibits excellent deformation capability, high sensitivity, good linearity, a wide strain detection range, and rapid response. It also possesses good biocompatibility, skin adhesion, and antibacterial properties, making it suitable for flexible wearable devices, medical health monitoring, and human-computer interaction. Furthermore, the flexible strain sensor proposed in this invention has a simple and reliable fabrication process, low manufacturing cost, and is suitable for mass production. Attached Figure Description

[0035] Figure 1 This is the sensitivity response curve of a flexible strain sensor.

[0036] Figure 2 This is the response time curve of a flexible strain sensor.

[0037] Figure 3 It is a 120-cycle test of a flexible strain sensor at 50% strain.

[0038] Figure 4 It refers to the tissue adhesion of flexible strain sensors.

[0039] Figure 5 It concerns the biosafety of flexible strain sensors.

[0040] Figure 6 It refers to the antibacterial properties of the flexible strain sensor. Detailed Implementation

[0041] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0042] Preparation Example 1

[0043] Preparation of polydopamine nanoparticles (PDA):

[0044] (1) Slowly add 2.0 mL of ammonia water (NH4OH, 28-30%, Sigma 221228) to a mixed solution of 40 mL of ethanol and 90 mL of ultrapure water. Stir the solution at 800 rpm for 30 min in the dark at 20 °C.

[0045] (2) Dissolve 0.5g of dopamine (Sigma H8502) in 10mL of ultrapure water, slowly inject the mixed dopamine solution into the above (1) mixed solution, and react at 20℃ for 24h.

[0046] (3) Centrifuge the solution from (2) after reaction at 12000 rpm at 20°C for 20 min and discard the supernatant. Wash the obtained product with ethanol and water. Resuspend the final polydopamine nanoparticles in ultrapure water and store at 4°C.

[0047] Preparation Example 2

[0048] Preparation of silver-loaded polydopamine nanoparticles (Ag@PDA):

[0049] (1) Silver nitrate (AgNO3, Aladdin S116265) was slowly added to ultrapure water and stirred for 30 min in the dark to obtain a mixed solution with a concentration of 5% (w / v).

[0050] (2) Slowly add ammonia water to the solution in (1) above, causing the solution to change from clear to turbid and then back to clear, and stir for 30 minutes in the dark.

[0051] (3) The polydopamine nanoparticles described in Preparation Example 1 were dispersed under ultrasonic conditions and slowly dropped into the mixed solution (2). The mixture was stirred at 500 rpm for 60 min in the dark at 20°C. The concentration of the polydopamine nanoparticles was 0.03% (w / v).

[0052] (4) Centrifuge the solution after reaction (3) at 12000 rpm at 20℃ for 20 min and discard the supernatant. Wash the obtained product with ethanol and ultrapure water, resuspend it in ultrapure water, and store it at 4℃.

[0053] Preparation Example 3

[0054] Preparation of gallic acidified chitosan (CSGA)

[0055] (1) Dissolve 1g of chitosan (CS, Sigma, 448877) in a solution containing 1% (v / v) acetic acid to obtain a chitosan solution with a mass fraction of 1% (w / v);

[0056] (2) Dissolve 1.37g gallic acid (GA, Aladdin, G131992) in 20mL of ethanol solution, 1.54g 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC, TCI, D1601) in 30mL of ultrapure water, and 0.93g N-hydroxysuccinimide (NHS, Sigma, 130672) in 10mL of ultrapure water. Mix the three solutions and add them dropwise to the solution in (1). Control the pH of the system to 5.1 and stir anaerobically at room temperature for 12h.

[0057] (3) The solution after reaction (2) was dialyzed in deionized water in a dialysis bag with a molecular weight cutoff of MWCO 14000 Da for 7 days, and then freeze-dried for 72 hours to obtain gallic acidified chitosan (CSGA) product, which was then sealed and stored at -20 degrees Celsius.

[0058] Preparation Example 4

[0059] Preparation of phenylboronicated chitosan (CSPBA)

[0060] (1) Dissolve 1g of chitosan (CS, Sigma, 448877) in a solution containing 0.5% (v / v) acetic acid to obtain a chitosan solution with a mass fraction of 1% (w / v);

[0061] (2) Dissolve 0.89g of 3-carboxyphenylboronic acid (PBA, Aladdin, C103261), 1.03g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, and 0.62g of N-hydroxysuccinimide (NHS, Sigma, 130672) in 50mL of methanol, and then add them dropwise to the solution in (1). Control the pH of the system to 6 and stir at room temperature without oxygen for 12h.

[0062] (3) The solution after reaction (2) was dialyzed in deionized water in a dialysis bag with a molecular weight cutoff of MWCO 14000 Da for 5 days, and then freeze-dried for 72 hours to obtain the product of phenylboronic chitosan (CSPBA), which was then sealed and stored at -20℃.

[0063] Example 1

[0064] Fabrication of a flexible strain sensor based on gallic acid-modified chitosan / phenylboronic acid-modified chitosan composite silver-loaded polydopamine nanoparticles (Ag@PDA-(CSPBA / CSGA)):

[0065] (1) Using a pipette, 10 mL of 10 wt% glycerol solution was drawn into a centrifuge tube, and 9 mg of the silver-loaded polydopamine nanoparticles described in Preparation Example 2 were added. The centrifuge tube was sonicated in an ultrasonic instrument for 8 min at a power of 600 W to ensure that the silver-loaded polydopamine nanoparticles were uniformly and completely dispersed in the 10 wt% glycerol solution. Subsequently, 0.2 g of the phenylboronic acid-modified chitosan described in Preparation Example 4 was measured using an analytical balance. The two were then placed in a beaker and stirred for 25 min until the phenylboronic acid-modified chitosan was completely dissolved in the glycerol solution containing 9 mg of silver-loaded polydopamine nanoparticles. Finally, the resulting solution was poured into a centrifuge tube and centrifuged at 2500 rpm for 15 min until the foam disappeared, yielding a brown solution A containing 2% phenylboronic acid-modified chitosan and 0.9 mg / mL silver-loaded polydopamine nanoparticles.

[0066] (2) Measure 0.2g of gallic acid modified chitosan as described in Example 3 using an analytical balance, measure 10mL of 10wt% glycerol solution, and then place both in a beaker and stir for 25min until the gallic acid modified chitosan is completely dissolved in the 10wt% glycerol solution. Finally, pour the resulting solution into a centrifuge tube and centrifuge at 2500rpm for 15min until the foam disappears, to obtain a colorless and transparent solution B containing 2% gallic acid modified chitosan.

[0067] (3) First, use a pipette to take equal volumes of solution A and solution B into centrifuge tubes, mix them in a vortex mixer for 40 seconds until they are evenly mixed, then centrifuge at 2000 rpm for 25 seconds in a centrifuge, and finally use a mold to prepare flexible sensors of various arbitrary shapes.

[0068] Test Example 1

[0069] Test Method: The Ag@PDA-(CSPBA / CSGA) flexible sensor prepared in Example 1 was fabricated into a dumbbell shape using a mold. The strain sensor was clamped at both ends with conductive copper wires. An external tensile force was applied to the strain sensor using a benchtop force gauge (Mark-10, 23-1030-09) and a vertically moving electric test bench (Mark-10, ESM303) at a stretching speed of 20 mm / min. Simultaneously with the stretching, the resistance change of the strain sensor under the applied tensile force was obtained using an impedance analyzer (Keithley, SMU Keithley 2400). The sensitivity was calculated using the resistance change rate (ΔR / R0) and strain change ε ​​during stretching, and linearity was obtained through linear fitting. The response time and recovery time were obtained by measuring the time interval between the 1% stretch and the significant resistance change when the sensor returned to its initial state. Cyclic stability testing was performed by cyclically stretching the strain sensor to 50% strain, and the cyclic and resistance change rate waveforms were obtained.

[0070] This invention verifies through experiments that the Ag@PDA-(CSPBA / CSGA) flexible strain sensor prepared by the above method can maintain R within a large strain range of 0 to 100%. 2 It exhibits good linearity of 0.999 and a sensitivity of 2.48 (e.g., ...). Figure 1 (As shown). This sensor has a fast response time of 263ms and a recovery time of 263ms (e.g. Figure 2 (As shown). This sensor exhibits good stability; after 120 tensile cycles within the 50% strain range, the output signal remains stable (as shown). Figure 3 (As shown).

[0071] Test Example 2

[0072] Test method: The adhesion of the Ag@PDA-(CSPBA / CSGA) flexible sensor prepared in Example 1 was characterized using a benchtop force gauge (Mark-10, 23-1030-09) and a vertically moving electric test bench (Mark-10, ESM303).

[0073] This invention verifies through experiments that the Ag@PDA-(CSPBA / CSGA) flexible strain sensor prepared by the above method has an overlap shear strength of 10.95 kPa (e.g., ...). Figure 4 As shown in the figure, it has good tissue adhesion.

[0074] Test Example 3

[0075] Test method: The Ag@PDA-(CSPBA / CSGA) flexible sensor prepared in Example 1 was subjected to a hemolysis experiment. The experimental setup included: a PBS group, Ag@PDA-(CSPBA / CSGA) groups with different concentrations (2 mg / mL, 4 mg / mL, and 6 mg / mL, respectively), and a Triton group (0.1% concentration). The specific procedure was as follows: 0.5 mL of each of the above groups was mixed with 0.5 mL of whole blood and incubated at 37°C for 1 hour. The red blood cell rupture was then observed.

[0076] This invention experimentally verifies that Triton's cell-permeable agent can significantly induce hemolysis, while the Ag@PDA-(CSPBA / CSGA) flexible sensor prepared by the above method exhibits good biocompatibility, consistent with the experimental results of the PBS group, and does not cause hemolysis (e.g., Figure 5 (As shown).

[0077] Test Example 4

[0078] This test case evaluates the antibacterial performance of the Ag@PDA-(CSPBA / CSGA) flexible sensor prepared in Example 1. The experimental setup included: a PBS group, an Ag@PDA-(CSPBA / CSGA) flexible sensor group, and an Ag@PDA-(CSPBA / CSGA) flexible sensor + near-infrared light irradiation group (near-infrared light wavelength 808 nm, power 1 W / cm²). 2 The irradiation time was 5 minutes.

[0079] The specific procedure is as follows: Using *Escherichia coli* (E. coli, ATCC25922) and *Staphylococcus aureus* (S. aureus, ATCC29213) as models, 10 μL of bacterial suspension (1×10⁻⁶) was prepared. 8 CFU / mL was added to each of the above groups in a 48-well plate (hydrogel volume 0.2 mL). After co-incubating with bacteria at 37°C for 2 h, 1 mL of PBS was added to each group and mixed thoroughly. Then, 100 μL of the bacterial suspension was transferred to an agarose culture plate and incubated at 37°C for 12 h. The bacterial growth was recorded by taking pictures.

[0080] The results are as follows Figure 6As shown, compared to the control PBS group, the Ag@PDA-(CSPBA / CSGA) flexible sensor exhibits a certain antibacterial effect. Furthermore, irradiating the Ag@PDA-(CSPBA / CSGA) flexible sensor with near-infrared light significantly inhibits bacterial growth, demonstrating a marked antibacterial effect with a sterilization rate exceeding 95%. These experimental results fully demonstrate that the Ag@PDA-(CSPBA / CSGA) flexible sensor prepared in this invention possesses excellent antibacterial properties.

[0081] The applicant declares that this invention illustrates a flexible strain sensor based on modified chitosan conductive hydrogel, its preparation method, and its application through the above embodiments. However, this invention is not limited to the above embodiments, meaning that this invention does not necessarily rely on the above embodiments for implementation. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of raw materials, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection and disclosure scope of this invention.

[0082] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.

[0083] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

Claims

1. A flexible strain sensor based on modified chitosan conductive hydrogel, characterized in that, The raw materials for preparing the conductive hydrogel flexible strain sensor include, by mass, 1-20 parts of modified chitosan and 0.1-2 parts of silver-loaded polydopamine nanoparticles; the modified chitosan includes gallic acid-modified chitosan and phenylboronic acid-modified chitosan; the mass ratio of gallic acid-modified chitosan to phenylboronic acid-modified chitosan is (0.5-2):(0.5-2).

2. The method for preparing a flexible strain sensor based on modified chitosan conductive hydrogel according to claim 1, characterized in that, The preparation method includes mixing a modified chitosan solution and a silver-loaded polydopamine nanoparticle solution to obtain the final product.

3. The method for preparing a flexible strain sensor based on modified chitosan conductive hydrogel according to claim 2, characterized in that, The preparation method specifically includes: (1) The silver-loaded polydopamine nanoparticle solution was sonicated and mixed with phenylboronic acid-modified chitosan by vortex mixing and centrifugation to obtain the first mixture; Gallic acid-modified chitosan was vortexed with a glycerol solution and centrifuged to obtain a second mixture. (2) Vortex mix the first mixture with the second mixture, then centrifuge to obtain the final product.

4. The method for preparing a flexible strain sensor based on modified chitosan conductive hydrogel according to claim 3, characterized in that, The ultrasound power is 300-800 W, and the duration is 1-10 min.

5. The method for preparing a flexible strain sensor based on modified chitosan conductive hydrogel according to claim 3, characterized in that, The silver-loaded polydopamine nanoparticle solution also includes glycerol.

6. The method for preparing a flexible strain sensor based on modified chitosan conductive hydrogel according to claim 5, characterized in that, The glycerol content by weight is independently 5-30%.

7. The method for preparing a flexible strain sensor based on modified chitosan conductive hydrogel according to claim 3, characterized in that, The duration of the vortex is independently 5-60 s.

8. The method for preparing a flexible strain sensor based on modified chitosan conductive hydrogel according to claim 3, characterized in that, The centrifugation speed in step (1) is 1000-4000 rpm and the time is 10-20 min.

9. The method for preparing a flexible strain sensor based on modified chitosan conductive hydrogel according to claim 3, characterized in that, In step (2), the centrifugation speed is 1000-4000 rpm and the time is 20-300 s.

10. The application of the flexible strain sensor based on modified chitosan conductive hydrogel according to claim 1 in flexible wearable devices, medical and health monitoring, or human-computer interaction.

Citation Information

Patent Citations

  • Antibacterial, adhesive and self-healing hydrogel as well as preparation method and application thereof

    CN114668897A

  • Polyphenol cross-linked natural polysaccharide-based hydrogel dressing as well as preparation method and application thereof

    CN115212345A